2021
DOI: 10.7551/mitpress/11577.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Consistency in Early Language Learning

Abstract: A data-driven exploration of children's early language learning across different languages, providing an empirical reference and a new theoretical framework. This book examines variability and consistency in children's language learning across different languages and cultures, drawing on Wordbank, an open database with data from more than 75,000 children and twenty-nine languages or dialects. This big data approach makes the book the most comprehensive cross-linguistic analysis to date of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
211
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(227 citation statements)
references
References 0 publications
15
211
1
Order By: Relevance
“…Yet while people were incredibly frequent in the child's view, animals -either as toys or their real-life versions -were relatively infrequent and occurred in equal proportions. This finding stands in contrast to a long literature documenting that even newborns prefer to attend to animate agents (Farroni et al, 2005), that visual cortex dedicates a remarkable amount of space to processing animals (Konkle & Caramazza, 2013), and that animal names tend to be among children's firstlearned words (Frank et al, 2021). Therefore, children's heightened attention to animals (Farroni et al, 2005) likely interacts with frequency of occurrence in the visual field to drive early category learning.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Yet while people were incredibly frequent in the child's view, animals -either as toys or their real-life versions -were relatively infrequent and occurred in equal proportions. This finding stands in contrast to a long literature documenting that even newborns prefer to attend to animate agents (Farroni et al, 2005), that visual cortex dedicates a remarkable amount of space to processing animals (Konkle & Caramazza, 2013), and that animal names tend to be among children's firstlearned words (Frank et al, 2021). Therefore, children's heightened attention to animals (Farroni et al, 2005) likely interacts with frequency of occurrence in the visual field to drive early category learning.…”
Section: Discussioncontrasting
confidence: 88%
“…Manual inspection of these frames containing animals revealed that the "real" animals had relatively little variety -they were overwhelmingly frames containing images of household pets (i.e., cats, dogs, and chickens, in the case of A), whereas the animals that were "toys/drawings" depicted a much larger variety of animals, as one might expect. Overall, these results suggest that -at least for these children -people are much more frequent than depictions or real-life versions of animals, indicating that toys and drawings may provide frequent input to their representations of these categories -despite the fact that animal names are often among children's first words (Frank, Braginsky, Yurovsky, & Marchman, 2021) and often referenced in storybooks.…”
Section: Resultsmentioning
confidence: 89%
“…This finding is hard to explain under any theory of language learning that requires very large amounts of TCDS input. While prior evidence predicts a highly robust onset of canonical babble (e.g., Oller et al 1995; Oller, Eilers, Neal & Cobo-Lewis, 1998; but see also Lee, Jhang, Relyea, Chen & Oller, 2018 and Cychosz et al, 2019), the stable use of individual phonological segments in speech-like babble and the subsequent appearance of recognizable words is indeed variable between children (McGillion, Herbert, Pine, Vihman, DePaolis, Keren-Portnoy & Matthews, 2017; see also McCune & Vihman, 2001) and, further on, children's early productive vocabulary size predicts their later syntactic development, including early word combinations (Frank et al, in press; Marchman et al, 2004). In sum, while prior evidence led us to expect a stable onset of canonical babble across diverse input contexts, it would not have led us to expect cross-context stability in the onset of early lexical productions, as found here.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of this experience with language (their “input”) is the basis for their lexical, grammatical, and sociolinguistic development. Much developmental language research focuses on the value of child-directed speech (CDS) in particular as a tailored source of linguistic input that can boost lexical and syntactic development (Bates & Goodman, 1997; Brinchmann, Braeken & Lyster, 2019; Frank, Braginsky, Yurovsky & Marchman, in press; Hart & Risley, 1995; Hoff, 2003; Huttenlocher, Waterfall, Vasilyeva, Vevea & Hedges, 2010; Lieven, Pine & Baldwin, 1997; Marchman, Martínez-Sussmann & Dale, 2004; Shneidman & Goldin-Meadow, 2012; Snow, 1977; Weisleder & Fernald, 2013). However, we have also known for decades that children's language environments – e.g., who is around and talking about what to whom – vary dramatically within and across families, and that children in some communities hear very little directed talk without any apparent delays in their linguistic development (e.g., Brown, 2011; Brown & Gaskins, 2014; de León, 2011; Gaskins, 2006; Ochs, 1988; Ochs & Schieffelin, 1984; Rogoff, Paradise, Arauz, Correa-Chávez & Angelillo, 2003; Schieffelin, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Parental reports systematically utilize parents' extensive experience with their children, and thus allow for the collection of data that is not just more extensive than what can typically be collected during a brief laboratory or clinical session, but that might also be more representative of children's abilities (Fenson et al, 2000). Furthermore, the application of parental reports, such as the widely-used MacArthur-Bates Communicative Development Inventories (CDIs) in cross-linguistic studies, has provided invaluable insight into infants' and toddlers' early lexical development (Bleses et al, 2008;Braginsky et al, 2019;Frank et al, 2021), while other studies have evinced predictive relationships between early vocabulary and subsequent academic outcomes (e.g., Bleses et al, 2016;Duff et al, 2015;Morgan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%